2009
DOI: 10.1111/j.1475-2743.2008.00189.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing extractable soil phosphorus methods in estimating phosphorus concentrations in surface run‐off from Calcic Hapludolls

Abstract: Understanding soil test phosphorus (STP) and surface run‐off phosphorus (P) relationships for soils is necessary for P management. The objective of the study was to evaluate the efficacy of various soil test indices to predict P losses in surface run‐off. Selected sites were subjected to in situ rainfall simulations according to the protocol of the National Phosphorus Research Project (NPRP, 2001). P from a composite of twenty‐four 2.0‐cm‐diameter core soil samples (0–5 cm) was extracted using the Olsen, Bray–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The enhanced responsiveness of resinextractable P over Olsen P was probably a reflection of the inability of the Olsen test to account for P in minerals such as apatite found in RPR (Rajan et al 1996;Saggar et al 1990). Schindler et al (2009) have recently suggested that for predicting P loss in surface runoff, agronomic tests like Olsen P (Olsen et al 1954) are as good as water-soluble P tests (McDowell & Condron 2004), which were designed specifically for the task. However, the Olsen P data in Table 1 suggest that no difference in surface runoff P concentrations would exist between treatments.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The enhanced responsiveness of resinextractable P over Olsen P was probably a reflection of the inability of the Olsen test to account for P in minerals such as apatite found in RPR (Rajan et al 1996;Saggar et al 1990). Schindler et al (2009) have recently suggested that for predicting P loss in surface runoff, agronomic tests like Olsen P (Olsen et al 1954) are as good as water-soluble P tests (McDowell & Condron 2004), which were designed specifically for the task. However, the Olsen P data in Table 1 suggest that no difference in surface runoff P concentrations would exist between treatments.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Veresoglou and Fitter (1984) carried out a study on nutrient uptake in five coexisting grasses and found that H. lanatus and A. capillaris could uptake 16.9 and 2.7 mg TP (m 2 .day) -1 , respectively. As WEP has strong linear relationship with TP concentrations in the runoff (Schindler et al 2009) and has been proved to be a useful indicator of soluble P concentrations in peat soil runoff water (Daly and Styles 2005), it is expected that the reduction of WEP in the grass seeded plots could result in reduction of P runoff release.…”
Section: Discussionmentioning
confidence: 98%